Magnetoacoustic Waves in a Dissipative Quantum Plasma With Spin-1/2 and Exchange-Correlation Effects - Loqman, Ibrahim G. H; Khaled, Mahmood A. H.; Alkuhlani, Kauther I (Journal of Amran University, 2022)
Using quantum magneto-hydrodynamic theory, the nonlinear propagation of magnetoacoustic waves have been investigated in a quantum magneto-plasma having dissipative ions fluid as well as quantum electrons and positrons, including exchange-correlation and electrons/positrons spin effects. The Korteweg-devris-Burger equation is derived employing the reductive perturbation method. It has been found that the quantum magneto-plasma system under consideration supports buth magnetoacoustic solitary and shock waves depending on the values of the plasma parameters. The effects of quantum plasma parameters (such as exchange-correlation coefficients, magnetic field strength, kinematic viscosity and the concentrations of electrons and positrons) on the magnetoacoustic shock waves (both monotonic shock waves and oscillatory shock waves) are examined. The profiles of both monotonic and oscillatory shock waves are found to be significantly affected by these parameters.The results of the current study may be useful to understand the properties of magnetoacoustic waves propagating in dense space plasma environments where the quantum mechanical effects of electrons and positrons are included.